Analisis Pengeluaran Tahunan Berdasarkan Laporan Keuangan Pada PT. Industri Kereta Api (INKA) - Maheswari Ivana Putri Cahyaningrum; Revania Anindhita Putri; Ravienda Anita Fitrie; Eva Hany Fanida (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the expenditure structure and annual expenditure changes trend at PT Industri Kereta Api (INKA), a manufacturing company in the railway sector. The research method employed is descriptive qualitative, utilizing a financial statement analysis approach based on secondary data from the company’s cash flow statements and supporting literature. The findings reveal that the company’s expenditure structure comprises direct costs, such as raw materials and labor, as well as indirect costs in the form of operational overhead. The analysis of cash flows from 2020 to 2024 indicates fluctuating expenditures, particularly a significant increase in investment activities in 2024. Additionally, operating cash flows exhibit instability, reflecting the dynamics of the company’s operational efficiency. Factors influencing expenditures include raw material prices, labor wages, government policies, and market demand. The implications suggest that while increased investment may support long-term production capacity development, suboptimal cost management could impact operational efficiency and company performance sustainability. Therefore, effective cost control strategies are essential to maintain financial stability and enhance the company’s competitiveness.